Beginning SQL Server 2012 for developers - Dewson, Robin ([New York] Apress New York Distributed to the book trade worldwide by Springer Science+Business Media, 2012)
Annotation Beginning SQL Server 2012 for Developersis the perfect book for developers new to SQL Server and planning to create and deploy applications against Microsofts market-leading database system for the Windows platform. Now in its third edition, the book is enhanced to cover the very latest developments in SQL Server 2012.Also new in the book is coverage of the no-cost Express Edition. Whether you have no knowledge of databases, or have knowledge of desktop databases such as Microsoft Access, or even come from another brand such as Oracle Database,BeginningSQL Server 2012 for Developersprovides the insights to get up and running with SQL Server 2012.Within the book, there are plenty of examples of tasks that developers routinely perform. Youll learn to create tables and indexes, and best practices for securing your valuable data. Youll learn design tradeoffs and find out how to make sound decisions resulting in scalable databases and maintainable code.Beginning SQL Server 2012 for Developerstakes you through the entire database development process, from installing the software to creating a database to writing the code to connect to that database and move data in and out. By the end of the book, youll be able to design and create solid and reliable database solutions using SQL Server 2012.Takes you through the entire database application development lifecycleIncludes brand new coverage of SQL Server 2012 featuresIntroduces the freely-available Express EditionWhat youll learnHow to install SQL Server 2012How to build a database application from start to finishHow to create tables and indices to manage your dataHow to write stored code to execute directly in the database serverHow to back up, recover, and otherwise maintain your databaseHow to connect to your database from client languages such as C# and VB .NETWho this book is forBeginning SQL Server 2012 for Developersis ideal for developers starting out with SQL Server 2012. There is no prerequisite background in developing database applications. Developers from other platforms and those brand new to database programming alike will find inBeginning SQL Server 2012 for Developersan excellent introduction to using and programming Microsofts database platform.Table of ContentsOverview and InstallationSQL Server Management StudioDatabase Design and CreationSecurity and ComplianceDefining TablesCreating Indexes and Database DiagrammingDatabase Backups and RecoveryDatabase MaintenanceInserting and Deleting DataSelecting and Updating DataBuilding a ViewStored Procedures, Functions, and SecurityEssentials for Effective CodingAdvanced T-SQLTriggersConnecting from Client Code
Overview and installation -- SQL server management studio -- Database design and creation -- Security and compliance -- Defining tables -- Creating Indexes and database diagramming -- Database backups and recovery -- Database maintenance -- Data insertion, deletion, and transactions -- Selecting and updating data -- Building a view -- Stored procedures, functions, and security -- Essentials for effective coding -- Advanced T-SQL and debugging -- Triggers -- Connecting via code
Includes index
1
Keywords: SQL server; Client/server computing; Data transmission systems; Database management